Frequency of PIK3CA mutations in different subsites of head and neck squamous cell carcinoma in southern Thailand - Arunee Dechaphunkul; Phatcharaporn Thongwatchara; Paramee Thongsuksai; Tanadech Dechaphunkul; Sarayut Lucien Geater (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Background Phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) mutations have been reported in many cancers, including head and neck squamous cell carcinoma (HNSCC). The frequency of these mutations varies among tumor locations and might be relevant to treatment outcomes among HNSCC. In this study, we examined the frequency of PIK3CA mutations in the different subsites of HNSCC. Methods Ninety-six fresh biopsy specimens were investigated for mutations in PIK3CA exons 4, 9, and 20 using allele-specific real-time polymerase chain reaction. Patient characteristics and survival were analyzed and compared between specimens with or without PIK3CA mutations. Results The study included primary tumors originating from the oral cavity (n = 63), hypopharynx (n = 23), and oropharynx (n = 10). We identified mutations in 10.4% of patients (10 of 96 specimens). The overall mutational frequency was 17.4% (4/23) and 9.5% (6/63) in the hypopharynx and oral cavity, respectively. No patients with oropharyngeal carcinoma had mutations. Among the 10 mutant specimens, five were missense mutations (exon 9 [E545K] in two samples and exon 20 [H1047R] in three samples) and five were silent mutations in exon 20 (T1025T). Mutations were not found in exon 4. Among 84 patients with available clinical data, we found no significant differences in clinical characteristics and survival based on the presence or absence of PIK-3CA mutations. Conclusions The results indicate that PIK3CA mutations are involved in HNSCC carcinogenesis, and the hypopharynx should be considered a primary site of interest for future studies, particularly in Southeast Asian populations.